2002
DOI: 10.1002/1521-3765(20020703)8:13<2838::aid-chem2838>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Biodendrimers: New Polymeric Biomaterials for Tissue Engineering

Abstract: Selective and efficient fluorination of organic 1,3‐dicarbonyl compounds was achieved using the electrophilic fluorinating reagents SelectfluorTM F‐TEDA‐BF4 (1‐chloromethyl‐4‐fluoro‐1,4‐diazoniabicyclo[2.2.2]octane bis‐tetrafluoroborate) in aqueous medium or AccufluorTM NFSi (N‐fluorobenzenesulfonimide) under solvent‐free reaction conditions (SFRC). Under both reaction conditions cyclic 1,3‐dicarbonyl compounds were transformed into 2‐fluoro‐substituted derivatives and acyclic analogues into 2,2‐difluoro‐subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 72 publications
0
125
0
Order By: Relevance
“…We have reported the synthesis and characterization of polyester, polyester-ether, and polyamide dendrimers and dendrons composed of biocompatible building blocks. [37][38][39][40][41][42][43][44][45][46][47][48] These dendritic polymers are termed "biodendrimers". Examples of a generation four poly( ) dendrimer terminated with hydroxyl groups ([G4]-P -OH), a generation three dendritic-linear copolymer terminated with hydroxyl groups (([G3]-P -OH) 2 -), and a generation two lysine-cysteine dendron ([G2]-) are shown in Figure 3.…”
Section: Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported the synthesis and characterization of polyester, polyester-ether, and polyamide dendrimers and dendrons composed of biocompatible building blocks. [37][38][39][40][41][42][43][44][45][46][47][48] These dendritic polymers are termed "biodendrimers". Examples of a generation four poly( ) dendrimer terminated with hydroxyl groups ([G4]-P -OH), a generation three dendritic-linear copolymer terminated with hydroxyl groups (([G3]-P -OH) 2 -), and a generation two lysine-cysteine dendron ([G2]-) are shown in Figure 3.…”
Section: Dendrimersmentioning
confidence: 99%
“…39,40,63 The specific polymer used was a dendritic linear copolymer composed of PEG, glycerol, and succinic acid like the one shown in Figure 3. The polymer was modified to contain terminal methacrylate (MA) groups and dissolved in a neutral aqueous solution.…”
Section: Photochemical Crosslinkable Adhesivesmentioning
confidence: 99%
“…The linear block mostly used in the synthetic strategy is poly(ethylene oxide) (PEO),and the dendrimers are poly(carbosilane) [4], poly(benzyl ester) [5], poly(aliphatic ester) [6][7][8], poly(triazine) [9,10] and poly(amidoamine) [1]. Amphiphilic copolymers with a linear hydrophilic block and hydrophobic dendritic blocks in selective solvent can form well-defined micelles.…”
Section: Introductionmentioning
confidence: 99%
“…We are synthesizing and evaluating dendrimers composed of natural metabolites such as glycerol and succinic acid for medical uses (34)(35)(36)(37)(38)(39). We have found that crosslinkable derivatives of these dendrimers are useful for the repair of ophthalmic wounds and articular cartilage (35,37,(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%